1998
DOI: 10.1093/bja/81.4.511
|View full text |Cite
|
Sign up to set email alerts
|

Local anaesthetic infiltration for surgical exodontia of third molar teeth: a double-blind study comparing bupivacaine infiltration with i.v. ketorolac

Abstract: We studied 40 patients undergoing surgical removal of at least two third molar teeth under general anaesthesia. Patients were allocated randomly to one of two groups: group B (n = 20) received bupivacaine up to 2 mg kg-1, infiltrated around the inferior alveolar nerves bilaterally, and group K (n = 20) received ketorolac 10 mg i.v. at the start of surgery. There were no significant differences between the two groups in postoperative pain scores measured at 1 h using a visual analogue scale. Group K had a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The longer duration of soft tissue anesthesia of bupivacaine is explained by its higher protein binding and pKa of 8.1 (6). The longer duration of the anesthesia could be unpleasant for patients and could cause difficulty eating, speaking, and a greater risk of soft tissue trauma (11,16,17). The duration of residual analgesia was higher for bupivacaine, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The longer duration of soft tissue anesthesia of bupivacaine is explained by its higher protein binding and pKa of 8.1 (6). The longer duration of the anesthesia could be unpleasant for patients and could cause difficulty eating, speaking, and a greater risk of soft tissue trauma (11,16,17). The duration of residual analgesia was higher for bupivacaine, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of long-acting intraoral local anesthetic can cause difficulty with speech and swallowing. Many authors consider that these unwanted effects detracts from its usefulness 13,18 . MELLOR et al 18 found no significant difference in analgesia between patients receiving bupivacaine infiltration versus intravenous ketorolac after third molar surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors consider that these unwanted effects detracts from its usefulness 13,18 . MELLOR et al 18 found no significant difference in analgesia between patients receiving bupivacaine infiltration versus intravenous ketorolac after third molar surgery. However, patients who received ketorolac reported a higher overall patient satisfaction compared with those who received bupivacaine only.…”
Section: Discussionmentioning
confidence: 99%
“…The longer duration of the anesthesia could be unpleasant for patients and could cause difficulty eating, speaking, and a greater risk of soft tissue trauma. 18,19 Articaine hydrolyzes rapidly, because it occurs both in plasma and liver. It is rapidly eliminated from the body, but the elimination of bupivacaine takes longer.…”
Section: Discussionmentioning
confidence: 99%